Serendipity Arts Festival 2019 : Projects Process- Volume IV (New Delhi; Serendipity Arts Foundation, 2019)
Projects/Processes is a new initiative to publish commissioned research essays, longform writing, and in-depth criticism that explore ideas and processes behind select curatorial projects at Serendipity Arts Festival.
English
Keywords: N4390-5098 Visual Arts. ExhibitionsIndia